Peran Walisongo dalam Perkembangan Islam di Jawa - Afandi, Afandi; Aziz, Abd (Javano Islamicus, 2024)
Islamic law (Sharia) and Sufi scholars, including the Walisongo, have been significant driving forces behind the development of a peaceful Islamic culture. The Walisongo exemplify how Islam evolved in Indonesia, particularly on the island of Java. As the early leaders of Islam, the Walisongo are revered throughout Java. Their contribution to the spread of Islamic da’wah in Indonesia in general, and in Java in particular, is an undeniable historical fact. This study employs a qualitative methodology. The qualitative research approach emphasizes the perspectives of research subjects and uses theoretical foundations as a guide to ensure that the research process aligns with the empirical facts discovered throughout the study. The initial process of Islam’s entry into Java successfully spread Islamic teachings across the island through a long and challenging journey. The term Walisongo, derived from the words wali (saint) and songo (nine), represents a group that played a vital role in bringing Islam to Java. The contribution of the Walisongo to Islamic education in Java is currently being revitalized and refined through more modern adaptations. The Walisongo stand as historical figures in Javanese Islamic education for their unique method of integrating Javanese culture and customs into their da’wah strategies, which effectively prevented Islamic education from being imposed through rigid processes of Islamization.